A Canonical Set of Operations for Editing Dashboard Layouts in Virtual Reality - Setti, Tarek; Csapo, Adam B. (Frontiers in Computer Science, 2021)
Virtual reality (VR) is a powerful technological framework that can be considered as comprising any kind of device that allows for 3D environments to be simulated and interacted with via a digital interface. Depending on the specific technologies used, VR can allow users to experience a virtual world through their different senses, i.e. most often sight, but also through touch, hearing, and smell. In this paper, it is argued that a key impediment to the widespread adoption of VR technology today is the lack of interoperability between users’ existing digital life (including 2D documents, videos, the Web and even mobile applications) and the 3D spaces. Without such interoperability, 3D spaces offered by current VR platforms seem empty and lacking in functionality. In order to improve this situation, it is suggested that users could benefit from being able to create reddashboard layouts (comprising 2D displays) black for themselves in the 3D spaces, allowing them to redarrange, view and interact with their existing 2D content alongside the 3D objectsblack. Therefore, the objective of this research is to help users organize and arrange 2D content in 3D spaces depending on their needs. To this end, following a discussion on why this is a challenging problem – redboth from a scientific and from a practical perspective black– a set of operations are proposed that are meant to be minimal and canonical and enable the creation of red dashboard black layouts in 3D. Based on a reference implementation on the MaxWhere VR platform, a set of experiments were carried out to measure how much time users needed to recreate existing layouts inside an empty version of the corresponding 3D spaces, and the precision with which they could do so. Results showed that users were able to carry out this task, on average, at a rate of red less than 45 seconds per 2D display black at an acceptably high precision.